Linking the online brand experience and brand credibility with tourists' behavioral intentions toward a destination. - Jiménez-Barreto, Jano; Rubio, Natalia; Campo, Sara; Molinillo-Jiménez, Sebastián (Elsevier, 2020)
Even though concepts such as brand experience and online brand credibility are critical in destination marketing strategies, there have been no previous studies that have analyzed their relationships and influence on tourists’ behavioral intentions. This paper develops a multimethod approach using a projective technique, an online experiment, and a multigroup analysis with five official destination platforms (the website, Facebook, Instagram, Twitter, and YouTube). The results confirm positive direct and indirect relationships among online destination brand experience (BE), perceived online destination brand credibility (PODBC), and users’ behavioral intentions toward the destination (intentions to visit/recommend). The multigroup analysis that was conducted revealed that users who had not visited the destination shaped their behavioral intentions by assigning a greater importance to the online destination BE than did those who had physically visited the destination. Conversely, users who had visited the destination showed a higher intensity in the path between PODBC and behavioral intentions.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/17162 (submitted version)
Keywords: Turismo - Aspectos sociales; Consumidores - Conducta; Medios de comunicación social; Brand experience; Destination brand; Destination website; Destination social media; Destination credibility